A Clinical Case Series of Acute and Maintenance Home Administered Transcranial Direct Current Stimulation in Treatment-Resistant Depression. Issue 2 (June 2022) - Le, Brandon; Alonzo, Angelo; Bull, Michael; Kabourakis, Michael; Martin, Donel; Loo, Colleen
Abstract : Objectives: Transcranial direct current stimulation (tDCS) is a noninvasive neurostimulation technique being translated clinically for the treatment of depression. There is limited research documenting the longer-term effectiveness and safety of tDCS treatment. This case series is the first report of remotely supervised, home-administered tDCS (HA-tDCS) for depression in a clinical setting. Methods: We report clinical, cognitive, and safety outcomes from 16 depressed patients who received acute and/or maintenance HA-tDCS. We retrospectively examined clinical data from up to 2.5 years of treatment. Descriptive statistics are reported to document patient outcomes. Results: Twelve patients received acute treatment for a current depressive episode and 4 commenced tDCS maintenance therapy after responding to ECT or repetitive transcranial magnetic stimulation (rTMS). The cohort was highly treatment-resistant wherein 15 of 16 patients failed 3 trials or more of antidepressant medication in the current episode, and 6 patients failed to gain significant benefit from prior ECT or rTMS. Five of 12 patients responded to acute tDCS within 6 weeks, and 9 patients who received tDCS for more than 12 weeks maintained improvements over several months. Cognitive tests showed no evidence of impairments in cognitive outcomes after up to 2 years of treatment. Two patients were withdrawn from treatment because of blurred vision or exacerbation of tinnitus. Transcranial direct current stimulation was otherwise safe and well tolerated. Conclusions: Transcranial direct current stimulation given for at least 6 weeks may be of clinical benefit even in treatment-resistant depression. Results provide support for long-term effectiveness, safety, and feasibility of remotely supervised HA-tDCS and suggest a role for maintenance tDCS after acute treatment with tDCS, rTMS, or ECT.